Meaning-Making through Education in the Slums: My Experiences - Haokip, T. Lhingneichin (THE PRIMARY TEACHER, 2019)
The concept, perception, and definition of slums vary across the states, depending on their socioeconomic conditions, but their physical characteristics are almost similar. Slums are usually a cluster of hutments with dilapidated and infirm structures having common toilet facilities, suffering from lack of basic amenities, inadequate arrangement for drainage, and disposal of solid waste and garbage (Slum Report, 2010: p.3). According to Encyclopaedia Britannica slums are “…residential areas that are physically and socially deteriorated and in which satisfactory family life is impossible…” Slums, hence, are not a conducive place to co-habit. And expecting the children from these ghettos to have quality education would be too tall an expectation. Needless to say, children in the slums are bound to miss basic life amenities that every normal child is expected to enjoy and cherish.